A RELATIONSHIP BETWEEN COMPLIANCE IN DRUG USE AND THE SUCCESS OF ANTIHYPERTENSION THERAPY IN THE INSTALLATION OUTPATIENT CARE AT TAWANGSARI COMMUNITY HEALTH CENTER, SUKOHARJO: RELATIONSHIP BETWEEN COMPLIANCE IN DRUG USE AND THE SUCCESS OF ANTIHYPERTENSION THERAPY IN THE INSTALLATION OUTPATIENT CARE AT TAWANGSARI COMMUNITY HEALTH CENTER, SUKOHARJO - Epaphroditus , Brian; Ovikariani; Retnowati (STIKES Telogorejo Semarang, 2024)
Abstract: The high incidence of hypertension in Indonesia is not followed by patient compliance in taking medication. The determinant of successful therapy is compliance with medication use. Low compliance levels cause problems such as increasing rates of chronic diseases and their complications. In 2019, the Tawangsari Sukoharjo Health Center was ranked eighth in Sukoharjo Regency with the largest number of hypertension patients, namely 1,583 people. This study aims to determine the relationship between drug compliance and the success of therapy in hypertension patients at the outpatient installation of Tawaangsari Health Center, Sukoharjo. This study is a descriptive observational study with a cross-sectional approach. Data collection was carried out using a purposive sampling method using the ASK-12 questionnaire in hypertensive patients who met the inclusion criteria. The research data were analyzed using chi-square statistics. The results showed that patients with high compliance were 45.7% while low compliance was 54.3%. The success rate of therapy was 55.7% of patients succeeded and 44.3% of patients failed. The results of the chi-square test showed a P value of 0.026 (P <0.05), which means that there is a relationship between compliance and the success of antihypertensive therapy in outpatient settings at the Tawangsari Health Center Keywords: Compliance level ; antihypertensive therapy ; therapeutic success